Correlation Between Ultrasonographically Estimated Fetal Weight and Actual Birth Weight in Females Presenting in a Tertiary Care Hospital - Rehman, Asif; Ihsan, Hussain Rashid; Khan, Usman Ali; Sharif, Sana; Anwar, Rabiah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the correlation between ultrasono-graphically estimated fetal weight and actual birth weight in females presenting in a tertiary care hospital.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Radiology Peripheral Nervous System, PNS Shifa Hospital Karachi Pakistan, from Sep 2018 to Jan 2019.Methodology: Fifty pregnant females were enrolled after meeting the inclusion criteria. A consultant radiologist calculated fetal weight by measuring biparietal diameter (BPD), head circumference (HC), femur length (FL) and abdominal circumference (AC) with the help of an ultrasound (USG) machine having a Hadlock 3 weight estimation algorithm. A paediatrician noted actual birth weight with a weighing scale after delivery.Results: The mean fetal weight on ultrasound was 2.52±0.34kg. The mean actual birth weight of the babies was 2.66±0.42 kg. A strong positive correlation (r=0.575, p